2012
DOI: 10.1111/jocs.12040
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Computed Tomography Coronary Angiography in the Management of Coronary Anomalies

Abstract: Congenital abnormalities of coronary arteries are an uncommon cause of sudden cardiac death and are difficult to detect at coronary angiography. We describe two patients with acute coronary syndrome and non-occlusive coronary artery disease in which a 64-multidetector computed tomography (MDCT) coronary angiography showed the presence of a malignant coronary anomaly. Sixty-four-MDCT with the possibility of 3D reconstructions allows for easier diagnosis of coronary anomalies and provides essential details neces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In a comprehensive review of patients undergoing coronary angiographic studies the incidence of coronary anomalies was 110/1950 = 5.6%, absent left main in 13/1950 = 0.67% and coronary arteriovenous fistula (CAVF) in 17/1950 = 0.87% [6]. In recent years, cardiac computed tomography (CCT) has become the test of choice for diagnosis of coronary anomalies [7]. In patients with atherosclerotic coronary artery disease presenting with acute coronary syndrome, surgical coronary revascularization can be safely associated with ligation excision of the CAVF.…”
Section: Discussionmentioning
confidence: 99%
“…In a comprehensive review of patients undergoing coronary angiographic studies the incidence of coronary anomalies was 110/1950 = 5.6%, absent left main in 13/1950 = 0.67% and coronary arteriovenous fistula (CAVF) in 17/1950 = 0.87% [6]. In recent years, cardiac computed tomography (CCT) has become the test of choice for diagnosis of coronary anomalies [7]. In patients with atherosclerotic coronary artery disease presenting with acute coronary syndrome, surgical coronary revascularization can be safely associated with ligation excision of the CAVF.…”
Section: Discussionmentioning
confidence: 99%
“…CTCA is a well-proven non-invasive imaging modality that provides an excellent overview of the cardiac vascular anatomy and high-resolution imaging of both origin and termination of fistulous tracts, allowing its complete depiction. Compared with CCA, CTCA can provide a more accurate assessment of coronary fistulas in less time, administering less contrast medium and avoiding burden and complications of arterial puncture and vascular catheterization [5] . On the other hand, indisputable advantage of CCA is the opportunity to perform intra-operative therapeutic maneuvers.…”
Section: Case Presentationmentioning
confidence: 99%
“…In patients with acute coronary syndrome sowing ambiguous ST segment changes on electrocardiogram, MDCT adds diagnostic accuracy and helps to exclude pulmonary embolism, aortic dissection, and other thoracic disease [31] . For patients with complex coronary artery disease who require bypass surgery, the 3D-image reconstruction from MDCT also provides additional details to operators [32] . Furthermore, it has been reported that the myocardial viability assessment derived from MDCT after primary revascularization may help to predict the clinical outcome in patients with AMI [22] .…”
Section: To the Editormentioning
confidence: 99%